Orthographic cueing in anomic aphasia: how does it work?...36th Clinical Aphasiology Conference, Ghent University, Ghent, Belgium, May 29th to June 2nd, 2006 - Lorenz A; Nickels L (Aphasiology)
Background: Both orthographic and phonological information from the target word can be appropriate cues in anomia treatment. Furthermore, both types of cues are used very frequently in clinical practice, although their underlying mechanisms of effectiveness and stability are still a matter of debate (e.g., Basso, Marangolo, Piras, & Galluzzi, 2001; Best, Herbert, Hickin, Osborne, & Howard, 2002; Howard & Harding, 1998). Aims: The aim of the study was to examine the mechanisms by which orthographic cues are effective in detail. The study addresses two questions. First, what is the relationship between sublexical transcoding ability and the effectiveness of orthographic cues? And second, what is the relationship between effectiveness of orthographic cues and effectiveness of phonological cues? Methods & Procedures: Three people with chronic aphasia and moderate to severe anomia participated in facilitation of spoken naming, using either the initial phoneme or initial letter of the target word. Both immediate and delayed effects were assessed over six facilitation sessions. Orthographic and phonological cue effects were investigated with regard to regularity of orthographic-phonological conversion (OPC) of the target's initial letter, and with regard to sub-lexical and lexical reading and repetition in the participants using a multiple single-case design (cf. Howard, 2003). Outcomes & Results: In one participant both phonological and orthographic cues produced similar effects. In the other two participants, orthographic cueing effects were present in the absence of phonological cueing effects. With regard to regularity of the initial letter-phoneme conversion in the orthographic condition, a similar pattern overall was present for regular, ambiguous, and irregular target words, e.g., initial letter cues seemed to be similarly effective in words such as KNIFE (irregular OPC of initial letter) as in words such as KING or DOLL. Conclusions: Initial letter cues are appropriate cues for the effective treatment of anomia as they may produce strong and long-lasting effects. In contrast to earlier predictions (e.g., Bruce & Howard, 1988), initial letter cues may be effective even in participants where the initial phoneme cue remains totally ineffective. There are likely to be various mechanisms of effectiveness underpinning orthographic cue effects: a sub-lexical mechanism and a lexical mechanism of effectiveness.